Purchasing Decisions on Eco-Friendly Products: A Study on Reusable Tumblers - Muhammad Randa Nurahman; Ali Akbar; Heru Suprapto; Erwinsyah Erwinsyah (Universitas Hamzanwadi, 2025)
The tumbler is considered an eco-friendly product because it can be refilled and reused multiple times, thereby reducing reliance on single-use plastic bottles. This research investigates how environmental awareness and perceived value affect students’ purchasing decisions for eco-friendly tumblers at Kutai Kartanegara University, with trust serving as a mediating variable. Using a quantitative, purposive sampling approach, data were collected from 92 active tumbler users via a structured questionnaire and analyzed using software SmartPLS 4.1.1.6. The study found that both environmental awareness and perceived value significantly and positively impact purchasing decisions and trust. This suggests that individuals with higher environmental awareness are more inclined to buy eco-friendly tumblers and are more likely to trust the environmental claims and qualities of these products. However, trust itself does not significantly influence purchasing decisions and does not mediate the link between environmental awareness, perceived value, and purchasing behavior. Therefore, the primary drivers of reusable tumbler purchases in this study were environmental awareness and perceived value.